2022
DOI: 10.3389/fonc.2022.949705
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the RNA-binding protein Musashi-2 is associated with immune infiltration and predicts better outcomes in ccRCC patients

Abstract: RNA-binding proteins (RBPs) mainly contribute to abnormalities in posttranscriptional gene regulation. The RBP Musashi-2, an evolutionarily conserved protein, has been characterized as an oncoprotein in various tumors. However, the prognostic value and potential roles of Musashi-2 in clear cell renal cell carcinoma (ccRCC) have not yet been elucidated. In this study, we found that Musashi-2 was mainly expressed in the normal distal tubular cells and collecting duct cells of the kidneys, while its expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…4 E). These results provide further evidence that MSI2 can reprogram tumor metabolism, protein translation and immune infiltration [ 13 , 16 ].
Fig.
…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…4 E). These results provide further evidence that MSI2 can reprogram tumor metabolism, protein translation and immune infiltration [ 13 , 16 ].
Fig.
…”
Section: Resultsmentioning
confidence: 64%
“…Our previous studies identified that MSI2 is involved in metabolic reprogramming-mediated immune infiltration in ccRCC [ 16 ] and immune dysregulation in DSS-induced colitis [ 17 ]. And recent study also confirmed that MSI2 can regulate immune-related signaling pathways in HCT116 and A549 cells, including TNF-α, inflammatory response and IFNG response pathway [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations